From big data to big analysis: a perspective of geographical conditions monitoring. (3rd July 2018) - Zhai, Liang; Zhang, Na; Hou, Wei; Feng, Zhixian; Qiao, Qinghua; Luo, Minghai
ABSTRACT: The idea of the geographical condition focuses on the analysis, study and description of the national condition from a geographical perspective. The first Census of National Geographical Conditions has now been completed in China. This census is the first phase in Geographical Conditions Monitoring (GCM). As a strategic direction for geographical information development in the era of big data, GCM is now facing the problem of how to use the massive amounts of geographical data to reflect the geographical conditions and to be the basis for the government to make or implement national development strategies and policies. Under this background, the concept of Geographical Conditions Monitoring Big Analysis (GCMBA) was proposed in this article. GCMBA can provide a new way to achieve the transformation from geographical data to geographical information and geographical conditions. In order to elaborate how to realise big analysis from the perspective of geographical conditions, the comprehensive analysis of regional natural ecological quality was taken as an example. The results showed that GCMBA was effective and useful in the transformation process of geographical data–geographical information–geographical conditions. Finally, this article presents some thoughts on conducting GCMBA.